2019
DOI: 10.1111/maps.13421
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and implications of secondary olivine veinlets in lunar highland breccia Northwest Africa 11273

Abstract: Lunar breccias preserve the records of geologic processes on the Moon. In this study, we report the occurrence, petrography, mineralogy, and geologic significance of the observed secondary olivine veinlets in lunar feldspathic breccia meteorite Northwest Africa (NWA) 11273. Bulk-rock composition measurements show that this meteorite is geochemically similar to other lunar highland meteorites. In NWA 11273, five clasts are observed to host veinlets that are dominated by interconnecting olivine mineral grains. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…2018; Zeng et al. 2020) implying that such metasomatic effects were common in nominally anhydrous bodies such as Vesta and the Moon. However, thermal metamorphism on Vesta might have erased those metasomatic features which may have formed in restricted areas on the parent body.…”
Section: Discussionmentioning
confidence: 99%
“…2018; Zeng et al. 2020) implying that such metasomatic effects were common in nominally anhydrous bodies such as Vesta and the Moon. However, thermal metamorphism on Vesta might have erased those metasomatic features which may have formed in restricted areas on the parent body.…”
Section: Discussionmentioning
confidence: 99%
“…The easier comminution of feldspar relative to for example, pyroxene or olivine has also been proven to be more effective with respect to impact experiments (Cintala & Hoerz, 1992;Hörz et al, 1984Hörz et al, , 2020. This, however, may only be applied to the regions where rocks similar to lunar anorthositic breccias are available, likely the highlands outside the South Pole-Aitken basin (Zeng et al, 2020). Hörz et al (2020) reported on the influence of micrometeorite impacts on the alteration of lunar surface rocks.…”
Section: Micro-flaking On the Surface Of Rocksmentioning
confidence: 99%
“…NWA 10447 is a regolith breccia meteorite consolidated from the surface materials on the Moon. By comparing this meteorite's composition with the global gamma ray spectroscopy geochemical data, the possible ejection regions of the lunar meteorite have been constrained (e.g., Calzada‐ Diaz et al, 2015; Gross & Joy, 2016; Joy et al., 2010; Zeng et al., 2018; Zeng, Li, et al., 2020). In this study, we used this geochemical data (i.e., FeO = 15.15 ± 1 wt%, TiO 2 = ± 1 wt%, and Th = 0.79 ± 1 ppm; Korotev and Irving, 2021; Table ) as input parameters to locate regolith samples that are compositionally similar to NWA 10447 (see Text for details).…”
Section: Discussionmentioning
confidence: 99%